A Regional Policy Alignment Framework for Standardizing Pharmaceutical Supply Chain Practices across ECOWAS Member States - Michael Aduojo Amuta; Muridzo Muonde; Ashiata Yetunde Mustapha; Akachukwu Obianuju Mbata (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Economic Community of West African States (ECOWAS) region faces persistent disparities in pharmaceutical supply chain governance, regulation, and logistics standards. This fragmentation contributes to inefficiencies, medicine stockouts, compliance challenges, and overall reduced access to essential medicines. This paper proposes a Regional Policy Alignment Framework (RPAF) to harmonize pharmaceutical supply chain practices across ECOWAS member states. The framework integrates regulatory convergence, logistical standardization, stakeholder coordination, and digital infrastructure to create a unified and resilient regional system. Drawing upon primary data from policy experts, health logistics managers, and regional regulatory agencies, as well as an extensive review of both academic and practice-based literature, the study applies a multi-level governance lens to assess feasibility and impact. Results demonstrate that alignment in policy structures significantly enhances cross-border pharmaceutical traceability, compliance, and inventory optimization. Moreover, the study highlights the critical role of ECOWAS regional institutions in driving regulatory harmonization through technical assistance and policy enforcement. The RPAF offers policymakers and stakeholders a structured, scalable pathway to achieving regional pharmaceutical supply chain integration and sustainable public health outcomes.